A META-ANALYSIS OF ISLAMIC MICROFINANCE : CASE BASED EVIDENCE FROM INDIA - Mohammad Irfan (Bank Indonesia, 2020)
This study examines Islamic microfinance as an important contributor to both the economic and human development of India. We are aware that conventional microfinance products have flourished in India; however, these products do not fulfil the needs of all Muslim clients. Taking small glimpses of Islamic microfinance (IMF), we can say it is working successfully in Muslim countries. From the meta-analysis we classify the literature into seven categories, viz. social benefits, religious values, business enterprises, poverty alleviation, sustainable development, rural development and economic development. The contribution of research papers has risen across the literature review and there has been a sharp rise in new facts pertaining to Islamic microfinance in India. As a diagnostic check, all seven factors of the meta-analysis of IMF contain evidence for the case study of India. Bait-un-Nasr is an urban co-operative credit society, located in Mumbai, India that has practised all of the factors extracted by the meta-analysis. This paper provides a roster of emerging projects accompanied by a comprehensive review of literature that will be useful to both academicians and practitioners for studying existing research and contemporary future research.